2018
DOI: 10.1097/jcp.0000000000000882
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Trihexyphenidyl (Artane) on Réunion Island

Abstract: This cohort describing the clinical characteristics of 69 patients is the largest cohort studied for THP addiction. Patients from the Centres for Addiction Prevention and Treatment were the youngest and most recently addicted, whereas general practice patients had been addicted for longer and were more socially integrated. This clinical description of THP addiction therefore enables us to identify the patients who are the most at risk, to set up an adapted care protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Benzhexol/Trihexyphenidyl (THP) was the most recorded abused anticholinergic drug ( Table 1 ). It has been covered by twenty-five articles, of which twelve were case reports [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], six case series [ 24 , 25 , 26 , 27 , 28 , 29 ], three observational study [ 30 , 31 , 32 ], two case control [ 5 , 33 ], one cohort study [ 34 ], and one survey [ 35 ]. Among the 12 subjects reported in the case reports, only two were female [ 21 , 22 ], while the overall age ranged from 19 [ 13 ] to 59 [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzhexol/Trihexyphenidyl (THP) was the most recorded abused anticholinergic drug ( Table 1 ). It has been covered by twenty-five articles, of which twelve were case reports [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], six case series [ 24 , 25 , 26 , 27 , 28 , 29 ], three observational study [ 30 , 31 , 32 ], two case control [ 5 , 33 ], one cohort study [ 34 ], and one survey [ 35 ]. Among the 12 subjects reported in the case reports, only two were female [ 21 , 22 ], while the overall age ranged from 19 [ 13 ] to 59 [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bipolar disorder [ 31 ], mixed personality disorder [ 24 ], anxiety [ 13 ], factitious disorder [ 32 ], schizoid disorder [ 33 ], unspecific mood disorder [ 32 ], attention deficit hyperactivity disorder (ADHD) [ 27 ], learning and intellectual disability [ 27 ], and intermittent explosive disorder [ 30 ] were reported by only one study ( Table 1 ). Finally, three studies reported unspecified mental illness [ 27 , 33 , 34 ]. Regarding the recorded psychiatric effects, disturbances of perception, in particular hallucinations/illusions, were the most frequently reported [ 14 , 15 , 17 , 18 , 19 , 20 , 24 , 27 , 28 , 31 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, current findings here did not identify any idiosyncratic intake modalities (e.g., intravenous use) that are typical of a substance misuse behavior. Hypothetically, putative levels of clozapine misuse liability might be tentatively explained considering the range of its pharmacodynamics activities, and the occurrence of rewarding and pleasurable effects due to the agonism at both delta-opioid [13,17,75] and cannabinoid CB1 receptors [18]; and the antagonism at muscarinic receptors [76,77]. Additionally, although clozapine was here ingested on its own in some 69% of cases, remaining antipsychotics and benzodiazepines were the drugs most frequently reported in association.…”
Section: Discussionmentioning
confidence: 99%
“…Sebuah studi kohort tentang penyalahgunaan triheksifenidil (Artane) di Pulau Reunion Prancis yang dilakukan pada 69 pasien penyalahguna triheksifenidil selama November 2016 melaporkan bahwa penggunaan triheksifenidil menyebabkan kecemasan (44%), gangguan perilaku (7%), tardive dyskinesia dan kerusakan gigi pada sebagian pasien. 28 Selain triheksifenidil, dextrometrophan juga merupakan jenis obat yang banyak disalahgunakan untuk tujuan rekreasional. Substance Abuse and Mental Health Services Administration (SAMHSA) melaporkan bahwa lebih dari 1 juta orang di Amerika menyalahgunakan dextrometrophan setiap tahun.…”
Section: Pembahasanunclassified